Motif System in Oral Narratives of Rural Population about Starvation in Ulyanovsk Volga Region in 1941-1945 - M. G. Matlin (Научный диалог)
The narratives on starvation in the rear during the Great Patriotic war on the territory of the Ulyanovsk Volga region are analysed. It is shown that they functioned primarily in the family sphere and were the means of transmitting not only life experience, but also family “symbolic capital.” The analysis of 43 oral stories found that they include a number of repeating and persistent motifs of different frequency. Different degree of development of motifs in the narrative is noted. Utterances about starvation typical to such texts which express the attitude of the narrator to events or associate the past experience with the time of telling are highlighted. The example of motivic organization is the analysis of oral story in which the motifs themselves, and some types of relations between them (thematic, associative) are most fully represented. It is shown that in some narratives some of these motifs are combined with references about various household details, descriptions of the experiences of the characters. The conclusion is that the narratives about Great Patriotic war can form complete plot that are separate stories or plot-compositional elements of a complex narrative.